2021
DOI: 10.1136/jitc-2021-003311
|View full text |Cite
|
Sign up to set email alerts
|

Trans-arterial chemoembolization as a loco-regional inducer of immunogenic cell death in hepatocellular carcinoma: implications for immunotherapy.

Abstract: BackgroundModulation of adaptive immunity may underscore the efficacy of trans-arterial chemoembolization (TACE). We evaluated the influence of TACE on T-cell function by phenotypic lymphocyte characterization in samples of patients undergoing surgery with (T+) or without (T-) prior-TACE treatment.MethodsWe profiled intratumoral (IT), peritumoral (PT) and non-tumoral (NT) background tissue to evaluate regulatory CD4+/FOXP3+ (T-reg) and immune-exhausted CD8+/PD-1+ T-cells across T+ (n=58) and T− (n=61). We perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
80
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 111 publications
(83 citation statements)
references
References 49 publications
3
80
0
Order By: Relevance
“…In line with our results, studies have shown decreased intra-tumoral T cells in HCC (36,37). TACE has been shown to decrease T cell infiltration regardless of treatment response (38) although the mechanisms remain unclear. Within the HCC-3 cohort, 50% of tumors were treatment naïve with 4 out of 5 patients having a treated tumor with complete pathological necrosis.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In line with our results, studies have shown decreased intra-tumoral T cells in HCC (36,37). TACE has been shown to decrease T cell infiltration regardless of treatment response (38) although the mechanisms remain unclear. Within the HCC-3 cohort, 50% of tumors were treatment naïve with 4 out of 5 patients having a treated tumor with complete pathological necrosis.…”
Section: Discussionsupporting
confidence: 91%
“…Similar to this study, we observed similar transcriptional profiles in multifocal disease regardless of treatment history. This is in agreement with a recent transcriptomic immune profiling of TACE treated versus untreated HCC which found only a single differentially expressed gene among the two groups (38). A majority of the immune panel used in that study (90%) contained genes on immune responses and lacked an inflammation signature, while 70% the panel used in this study focused on tumor signaling pathways and included the inflammation signature.…”
Section: Discussionsupporting
confidence: 89%
“…Jiang et al have found that metformin triggers the NF-κB signal pathway, which leads to caspase-3/GSDME-mediated cancer cell death [48]. Many recent attempts to increase effectiveness by combining TACE and targeted treatment with immunotherapy have been documented [49][50][51][52]. As a local chemotherapy modality, TACE can promote better immunotherapy by modulating the TIME [50].…”
Section: Discussionmentioning
confidence: 99%
“…Many recent attempts to increase effectiveness by combining TACE and targeted treatment with immunotherapy have been documented [49][50][51][52]. As a local chemotherapy modality, TACE can promote better immunotherapy by modulating the TIME [50]. Several sensitive drugs were proven to target the four genes associated with pyroptosis.…”
Section: Discussionmentioning
confidence: 99%
“…In the 58 patients with pre‐procedure TACE, intra‐tumoral samples showed significantly lower expression of CD4 + /FOXP3 + and CD8 + /PD‐1 + , both predictors of improved recurrence‐free survival. In a subset of 24 patients with viable tumour on histology, those treated with TACE demonstrated significant upregulation of interferon‐regulated transcription factor 2 (IRF2) which is a transcriptional repressor of PD‐L1 and regulator of a number of components of the Major Histocompatibility Complex‐I pathway 29 . This suggests TACE increases intra‐tumoral inflammation and may have a role in activating initial tumour antigen expression which could augment immunotherapy if given in combination.…”
Section: Immunotherapy and Transarterial Therapy For Hcc—what Is On T...mentioning
confidence: 99%